Nontraditional grain sources in brewing and effects on wort and beer - Reed, Aaron (Kansas State University, 2016)
Brewing of beer has a long history and has evolved over time as tastes, markets and science have progressed. Traditionally malted barley is the grain source used in brewing. Malt provides a multitude of benefits including: fermentable carbohydrates, nitrogen for yeast metabolism, color compounds, flavor compounds and minor constituents that provide for various qualities in beer such as foam and colloidal stability. There is, however, interest from brewers and drinkers alike for a variety of beer styles. Because of this and other reasons, brewers have worked with adjuncts such as oats, sorghum, wheat, rice, and maize. These grains can be used in unmalted or malted forms, but the incorporation of these grains affects the brewing process and final beer qualities. A review of literature reveals the use of grains other than malted barley reduce the nitrogen contribution and alter the amino acid profile available for yeast metabolism, leading to slower fermentations and variations in the fermentation products resulting in changes to beer flavor. Exceptions include sorghum and oats, which provide a more beneficial amino acid profile than barley despite lower levels of nitrogen when compared to barley. Extract is found to increase when using maize and rice, while oats and sorghum reduce the amount of extract. Wheat has comparable extract to barley. Grains that contribute B-glucans and arabinoxylans will increase viscosity, while grains without these components will reduce viscosity if fermentation is complete. Additionally, most grains will reduce the foam stability due to altered nitrogen and protein contributions; wheat being the lone exception that improves foam stability. This review will discuss the above mentioned attributes and more to explore the changes to be expected when brewing with unmalted and malted grains other than barley.
Keywords: beer; wort; mash; brewing; wheat; maize; rice; corn; sorghum; barley; malt; adjunctcereal grain